Optimizing strategies to prevent HIV transmission through breastfeeding in sub-Saharan Africa, a mixed approach - (:unkn) unknown (My University, 2024)
Despite the progress made over the last 20 years in preventing new paediatric HIV infections, the elimination of mother-to-child transmission (MTCT) is currently unattainable, especially in sub-Saharan countries where 89% of MTCT cases occurs. International guidelines are hesitant to adopt infant post-natal prophylaxis (PNP) beyond 12 weeks of life, due to a lack of scientific data on the benefit/risk balance. However, several African countries have already included extended PNP in their recommendations. In order to limit unnecessary exposure of children to antiretroviral prophylaxis, one strategy is to initiate PNP only in cases of high maternal viral load (VL). Through a phase II clinical trial in Burkina Faso (PREVENIR-PEV), followed by a phase III randomized clinical trial in Burkina Faso and Zambia (PROMISE-EPI), we evaluated the efficacy and safety of a prevention package for postnatal HIV transmission. This package included measurement of maternal CV using a point-of-care (POC) test with immediate results, and -drug prophylaxis (lamivudine) initiated in breast-fed infants whom maternal CV was ≥1000 cp/mL. A parallel qualitative study explored the facilitators and barriers of this prevention package. No MTCT occurred in the PREVENIR-PEV trial, which included only one intervention arm, out of 78 children followed up to 12 months. In the PROMISE-EPI trial, the incidence of transmission was 0.19 per 100 person-years (PY) in the intervention arm and 1.16 per 100 PY in the standard-of-care arm (p=0.066). The number of serious adverse events was identical in both arms. The qualitative study identified 1) more barriers to the triple-drug prophylaxis made available by the Zambian government than to the single-drug prophylaxis offered in PROMISE-EPI, 2) that the virtuous circle induced by the use of POC with immediate medical decision could rapidly reverse into a vicious circle in the event of sub-optimal POC testing. The prevention package used in PREV
Keywords: African Research